Does Productivity Rise Faster in the United States? - MacDougall, G. D. A. (The Review of Economics and Statistics, 1956)
IT is widely believed that productivity normally increases substantially faster in the United States than it does elsewhere, but a survey of the relevant statistics relating to the present century suggests that this is far from certain, at least in peacetime. It may be that we sometimes suffer from an optical illusion in this matter. We can, for example, easily be misled by comparing a recent prewar year (such as I937 or the average of I934-38), when the United States was depressed, with a postwar year like I949 or I950, when the rest of the world had not fully recovered from the war. In making comparisons of Britain and America we can also be misled if we ignore the rapid growth in the American population, which is increasing by nearly one million every four months. In I955 it was 28 per cent greater than in I937, a year often used for comparisons with the present. During the same period the United Kingdom population rose by only 8 per cent. Britain, moreover, has probably been less successful in raising productivity than many other countries. And, perhaps most important of all, we may not always take sufficient account of the two world wars which have played such havoc with the economies of many nations outside the United States. We are of course discussing proportionate rates of growth in productivity. It is undeniable that the absolute level of productivity and the absolute annual increase in output per head are much higher in the United States than in most other countries; and the absolute gap in living standards is steadily widening. This raises important economic and political problems, but it is not the question at issue here. It should be noted that the diagrams throughout this article are drawn on semi-logarithmic, or ratio, scales so as to show proportionate, rather than absolute, changes in the magnitudes portrayed. We shall have to examine the behavior of a good many index numbers, and a once-for-all warning and apology at this stage will avoid tedious repetition. Index numbers are, for good theoretical reasons, notoriously and inevitably dangerous to interpret, especially when longterm trends are in question; and some of the figures we shall have to use are in addition based on shaky estimates and of doubtful comparability. To some extent this is inevitable. Better basic figures, at least about the past, may never be available. But there is also scope for more careful exploration of the data that exist (including statistics bearing indirectly on the subject and nonstatistical information as well) than was possible for our present purpose. It is to be hoped that others will attempt this task, but, in the meantime, we must seek provisional conclusions from the figures presented in the following pages. It is certainly impossible to form a judgment without any figures at all; for, as we shall see later, there is no clear a priori reason why productivity should increase much faster in the United States than it does elsewhere. The statistics that follow exclude Russia and China throughout, and usually the countries of Eastern Europe after I939 1 (the index numbers have then, of course, been linked at a prewar year, and so require no upward adjustment in postwar years to give a true picture of rates of growth). We start with a summary of production (not productivity) of raw materials, foodstuffs, and manufactures in the United States and in the * This paper will appear, in a somewhat different form, as a chapter in a forthcoming book on the dollar problem to be published by Macmillan. It will be supported by an Appendix but, since this is as long as the text itself, it has not been possible to reproduce it here. The references to it have, however, been retained so that the reader may have some idea of the statements and figures that are more fully explained in it. The conclusions reached here should not be taken to imply that there is, or is not, a long-run dollar problem; the relation between rates of growth of productivity in different areas and the balance of payments between them is a complex one. No account is taken in this paper of possible differences in rates of innovation. I am greatly indebted to Miss Monica Verry and Mr. Maurice Scott for invaluable assistance and to many others who have commented on the draft. The exception is the index of raw material production, where it was statistically more convenient to include Eastern Europe throughout.